2010
DOI: 10.1007/s12012-010-9079-6
|View full text |Cite
|
Sign up to set email alerts
|

Purine Bases Oxidation and Repair Following Permethrin Insecticide Treatment in Rat Heart Cells

Abstract: Pollutants including insecticides have been recently reported to be a risk factor involved in various diseases. Permethrin, a member of the family of synthetic pyrethroids, is widely used as insecticide in agriculture and other domestic applications. To investigate possible cardiotoxicity, we had examined different concentrations of permethrin on the freshly isolated rat heart cells using the alkaline comet assay. A significant difference in % tail DNA between all concentrations of permethrin (5, 10, 20 microM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 48 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Romero and his team showed that Cypermethrin, one of the prethyroid insecticides, causes apoptotic, necrotic and autophagic cell death by inducing oxidative stress that causes DNA damage in neuroblastoma cells (Romero et al, 2017). Although the target organs of prethyroids are different, Perm-mediated oxidative stress has been shown in humans and animals caused neurotoxicity (Nasuti et al, 2014), hepatotoxicity (Roma et al, 2012), nephrotoxicity (Guvenc et al, 2013), immunotoxicity (Jin et al, 2010), cardiotoxicity (Dhivya Vadhana et al, 2010). However, Res is a molecule that shows antioxidant potential by destroying free radicals, binding metal ions, decreasing the activity of enzymes involved in the formation of reactive oxygen species, and increasing antioxidant enzyme activities (Chen et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Romero and his team showed that Cypermethrin, one of the prethyroid insecticides, causes apoptotic, necrotic and autophagic cell death by inducing oxidative stress that causes DNA damage in neuroblastoma cells (Romero et al, 2017). Although the target organs of prethyroids are different, Perm-mediated oxidative stress has been shown in humans and animals caused neurotoxicity (Nasuti et al, 2014), hepatotoxicity (Roma et al, 2012), nephrotoxicity (Guvenc et al, 2013), immunotoxicity (Jin et al, 2010), cardiotoxicity (Dhivya Vadhana et al, 2010). However, Res is a molecule that shows antioxidant potential by destroying free radicals, binding metal ions, decreasing the activity of enzymes involved in the formation of reactive oxygen species, and increasing antioxidant enzyme activities (Chen et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal exposure also caused cardiotoxicity, reduced heart size, and increased calcium influx in cardiac cells that was apparent much later in life (500 days old) 23 . When isolated rat heart cells were incubated with permethrin, DNA damage and physiochemical changes were observed 24,25 . Permethrin exposure can also have intergenerational effects.…”
Section: Introductionmentioning
confidence: 99%
“…Although not extensively studied, research shows exposure to pyrethroid compounds at doses below those that have effects in adults can negatively affect early development in mammalian models, causing changes in skeletal, brain, and heart morphology. 12,14,[21][22][23][24][25] Oral administration of permethrin or deltamethrin, another pyrethroid commonly used as a pesticide, in pregnant rats and rabbits caused greater loss of developing fetuses, reduced fetal body weight and limb size, high frequencies of fetal skeletal abnormalities, and fetal microcephaly, microphthalmia, and tissue necrosis of the brain. 14,21 Treatment of neonatal rats with permethrin impaired long-term memory, 12 and caused changes in gene expression in the brain.…”
mentioning
confidence: 99%
See 1 more Smart Citation